Academic androcentrism: the fiction of neutral knowledge - Laura Nuño Gómez; Enrique Álvarez Conde (Feminismo/s, 2017)
Spanish universities have a normalized presence of women and are bound by law to incorporate gender studies and a non androcentric perspective in teaching and research. Nevertheless, ceilings and glass walls remain, gender studies have not been mainstreamed and the different disciplines have androcentric views on knowledge. After the adoption of the so-called Bolonia Plan, far from implementing the legal duty, the treatment provided to gender studies in the Higher Education system has been peripheric. This article adresses this situation in public universities, highlights some problematic elements as well as possible solutions.